Analecta Septentrionalia: Beiträge zur nordgermanischen Kultur- und Literaturgeschichte - Heizmann, Wilhelm; Schier, Kurt (Ergänzungsbände zum Reallexikon der germanischen Altertumskunde, 2009)
Compared to other medieval philologies, the particular nature of the literature of the North, and in particular of Iceland, has always meant that the study of Old Norse languages must be interdisciplinary and rely on methodical variety. This volume, published on the occasion of the 80th birthday of the Munich old Norse scholar, Kurt Schier, contains some three dozen studies on the mythology, history of religion, literature and poetry of the North, as well as runic and onomastic studies, and so reflects the broad thematic spectrum of modern old Nordic studies